What we know about grief intervention: a bibliometric analysis - Li, Jie; Li, Yuan; Wang, Yali; Jishi, Wuga; Fang, Jinbo (Frontiers in Psychiatry, 2023)
Background Grief is a natural and individualized response to different losses, but if grief persists or becomes pathological, professional interventions are required. Grief and corresponding interventions have received increasing attention, as the related concepts have been incorporated into the DSM-5 and ICD-11. Therefore, we conducted a bibliometric analysis to explore the developments in the field of grief intervention research. Methods Articles on grief interventions were systematically searched and screened from the Web of Science Core Collection. The retrieved data were analyzed and visualized using VOSviewer and Bibliometrix software for journals, authors, institutions, countries, references, and keywords. Results A total of 9,754 articles were included. The number of articles on grief interventions has increased significantly each year since 1990. Death Studies was the journal that published the most articles in this field. We identified 25,140 authors contributed to this research area and these authors were from 123 countries and 6,630 institutions. Boelen PA secured the first position in article production, Columbia University emerged as the most productive affiliation and the United States was the foremost leading in grief intervention research. The prevalent keywords utilized in this field comprised bereavement, grief, death, depression, and palliative care. Conclusion The quantity of publications regarding grief interventions is increasing. Although most prior studies have focused on mortality, grief, and health, emerging themes such as COVID-19, grief among workers, and disfranchised grief have drawn increasing attention in recent years. Future studies may focus on investigating the complexities and challenges of grief, including its underlying mechanisms and impact on mental well-being.